Evaluation of spider lilies (Hymenocallis spp.) as sentinel plants for orthotospoviruses - Hsu-Yao Chao; Ralf G. Dietzgen; John E. Thomas; Andrew D. W. Geering (Phytopathology Research)
Abstract Spider lilies (genus Hymenocallis) are perennial herbaceous plants native to tropical and subtropical America and are popular landscaping plants in similar climes throughout the world. They are susceptible to infection by at least five different orthotospoviruses, and display prominent symptoms of infection, suggesting that they may be useful as sentinel plants for monitoring the presence of orthotospoviruses in the environment. In this study, surveys of spider lilies for orthotospoviral infections were done in three distinct Queensland regions. In southeast Queensland, spider lilies infected by tomato spotted wilt virus (TSWV) were found at 65 locations, whereas spider lilies infected by capsicum chlorosis virus (CaCV) were only found at two locations. Conversely, in central and far north Queensland, CaCV-infected spider lilies were found at 41 locations, while TSWV-infected spider lilies were only found at two locations. Phylogenetic analyses based on the complete nucleocapsid protein sequences indicated a population structure of the virus isolates that correlated with the geographical origins of the samples. Both non-systemic and systemic TSWV infections were identified in spider lilies, and some initially non-systemically infected spider lily plants ended up with systemic infection. We demonstrated that Taeniothrips eucharii (Whetzel), a common thrips species on spider lilies in southeast Queensland, can transmit TSWV and has likely amplified TSWV infections in spider lilies in this region. Overall, the results of this study suggest that spider lilies could be useful sentinel plants for indicating the presence of orthotospoviruses in the environment.